Self-programming of neural networks for indexing and function approximation tasks - Zaremba, Marek B.; Porada, Eugeniusz (Zielona Góra: Uniwersytet Zielonogórski)
The problem of non-iterative mapping of stimulus-response associations directly onto an association matrix is addressed in this paper. The procedures presented are designed for the calculation of connection weights in multilayer, feedforward neural networks. Two distinct situations from the standpoint of object separability are analyzed in more detail.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka